2001
DOI: 10.1016/s0014-5793(01)02787-9
|View full text |Cite
|
Sign up to set email alerts
|

FKBP12 associates tightly with the skeletal muscle type 1 ryanodine receptor, but not with other intracellular calcium release channels

Abstract: This study compared the relative levels of ryanodine receptor (RyR) isoforms, inositol 1,4,5-trisphosphate receptor (IP 3 R) isoforms, and calcineurin, plus their association with FKBP12 in brain, skeletal and cardiac tissue. FKBP12 demonstrated a very tight, high affinity association with skeletal muscle microsomes, which was displaced by FK506. In contrast, FKBP12 was not tightly associated with brain or cardiac microsomes and did not require FK506 for removal from these organelles. Furthermore, of the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 41 publications
2
41
1
Order By: Relevance
“…The DHPR copurifies with, and is a substrate of, calcineurin (Sacchetto et al 2002). In addition, Carmody et al (2001) showed that the RyR1 isoform in skeletal muscle tightly associates with the FK506 binding protein FKBP12. FKBP12 is the target of the calcineurin inhibitors FK506 and cyclosporine.…”
Section: Calcineurin Distribution In the Cytoplasm During Muscle Devementioning
confidence: 99%
“…The DHPR copurifies with, and is a substrate of, calcineurin (Sacchetto et al 2002). In addition, Carmody et al (2001) showed that the RyR1 isoform in skeletal muscle tightly associates with the FK506 binding protein FKBP12. FKBP12 is the target of the calcineurin inhibitors FK506 and cyclosporine.…”
Section: Calcineurin Distribution In the Cytoplasm During Muscle Devementioning
confidence: 99%
“…In these experiments, the FKBP and pc-MycRyR2C plasmids were co-expressed in HEK293 cells, and evidence for binding was monitored by assaying the amount of FKBP cosedimenting with the microsomal membrane fraction. Centrifugation-based binding assays are often used in situations of rapid ligand dissociation and low affinity, because the receptor and ligand remain in equilibrium throughout the separation period, and they have been used for the study of the RyR-FKBP association (27,29,43,44), as well as the RyR-calmodulin interaction (45). In addition, the assay takes place in a detergent-free environment where the RyR2 C-terminal fragment is most likely to retain a native conformation.…”
Section: Ryr2 C-terminal Fragments Compete For Fkbp126mentioning
confidence: 99%
“…While it is striking that the structural differences between two isoforms of a protein arises from just one residue change out of 18, there may be significance for the functional differences between FKBP12 and FKBP12.6. FKBP12 associates with the skeletal ryanodine receptor (RyR1), while FKBP12.6 selectively binds the cardiac ryanodine receptor (RyR2) (Carmody et al, 2001;Gaburjakova et al, 2001;Xin et al, 1999). Ryanodine receptors govern the release of Ca 2+ from the sarcoplasmic reticulum in skeletal and heart muscle, thus triggering muscle contraction (Gaburjakova et al, 2001).…”
Section: Increased Stability Of Mutants Suggests a Tradeoff Betweenmentioning
confidence: 99%
“…FKBP12-FK506/rapamycin complexes inhibit key events in the cytoplasmic signal process, leading to immunosuppression (Schreiber, 1991). FKBP12 and its isoform FKBP12.6 have been found to be crucial regulators of intracellular Ca 2+ release due to their association with ryanodine receptors, thus playing essential roles in excitation-contraction coupling in skeletal and cardiac muscle (Jayaraman et al, 1992;Brillantes et al, 1994;Xin et al, 1999;Carmody et al, 2001;Gaburjakova et al, 2001). Disruption of the FKBP12.6 gene in mice results in cardiac hypertrophy (Xin et al, 2002), while developmental cardiac defects have been reported in FKBP12-deficient mice (Shou et al, 1998).…”
mentioning
confidence: 99%